Microsatellite instability in patients with hepato-biliary-pancreatic malignancies in clinical practice (KHBO 1903) - Kubo, Shoji; Nagano, Hiroaki; Tsujie, Masanori; Seo, Satoru; Gotoh, Kunihito; Wada, Hiroshi; Nakashima, Shinsuke; Ioka, Tatsuya (International journal of clinical oncology, 2022)
Background This study aimed to determine the prevalence of microsatellite instability (MSI)-high status in hepato-biliary-pancreatic malignancies in clinical practice and the clinical characteristics of and therapeutic results of pembrolizumab on patients with MSI-high cancers. Methods The subjects were 283 patients who had undergone MSI tests for unresectable, metastatic hepato-biliary-pancreatic malignancies at seven hospitals. The tests were polymerase chain reaction fragment analyses using the microsatellite markers consisting of BAT25, BAT26, NR21, NR24, and MONO27. Formalin-fixed, paraffin-embedded blocks, prepared according to the guidelines of the Japan Society of Pathology were used within 4 years after sampling. There were 13 patients with cancers high in MSI, including eight patients receiving pembrolizumab treatment. The clinical characteristics of these patients and therapeutic outcomes of their pembrolizumab treatment were investigated. Results MSI-high was detected in 13 (4.6%) of the 283 patients with hepato-biliary-pancreatic malignancies. None of these 13 patients had been diagnosed with Lynch syndrome. Of the Eight patients receiving pembrolizumab, a complete response was observed in three patients, a partial response in one patient, and stable disease in three patients. The objective response rate was 50% and the disease control rate was 87.5%. Conclusion MSI-high was detected in 4.6% of patients with hepato-biliary-pancreatic malignancies. There was a 50% objective response rate to pembrolizumab treatment for MSI-high cancers. The evaluation of MSI status by the current method using appropriately prepared tissue samples was to be a reliable and accurate approach to both the determination of MSI status and estimation of the effectiveness of pembrolizumab.